Adoption of agile methodology for improving IT project performance - Rajan, Eldho Roshan; Santhosh, Vijayakumar Ambujakumari (Serbian Journal of Management, 2021)
Most of the IT organizations are facing various challenges such as technological advancement, new customer requirements, merger & acquisition, and changing market demands, which should be addressed to survive in the industry. For enhancing more value to the customer in the project, the best option is to choose Agile Methodology for managing the project, which helps to accommodate the ad-hoc business requirement than pre-planned. Though, most of the organization, especially in the IT industry is shifting to Agile methodology practice, which helps to enjoy the benefit of better collaboration and customer experience. The study was conducted among 404 IT professionals from the IT corridors of India to understand the influence of Agile methodology on IT project performance. Most responses received from people who have sound experience in IT project management which assures the quality of results obtained. From study, it has been found that Agile methodology (β= 0.630, p
Keywords: scrum; agile methodology; project performance; adoption